Plasmatic free light chains in polycystic ovary syndrome. (3rd August 2019) - Mancini, Antonio; Brunetti, Alessandro; Bruno, Carmine; Vergani, Edoardo; Pocino, Krizia; Napodano, Cecilia; Gulli, Francesca; Santini, Stefano Angelo; Basile, Umberto
Abstract: Polycystic ovary syndrome (PCOS), as systemic disease, is accompanied by different indexes of inflammation. Free light chains of immunoglobulins (FLCs), produced by plasmacells, are released in slight excess for the immune requests, with still poorly defined physiological role but surely they represent a marker of inflammation. In order to evaluate their levels and correlate them with hyperandrogenism, we have studied a group of PCOS patients, age range 18–37 yrs, mean ± SEM body mass index (BMI) 24.1 ± 0.9 kg/m 2 ), compared with age- and BMI-matched controls, with assay of k and λ FLCs, by turbidimetric method, and their ratio in blood plasma. PCOs exhibited higher levels vs. controls: (mean ± SEM λ : 10.0 ± 0.85 mg/L vs. 8.41 ± 0.45 mg/L; k : 12.45 ± 0.72 mg/L vs. 6.41 ± 0.34 mg/L; k / λ : 1.31 ± 0.07 vs. 0.78 ± 0.04). A significant direct correlation was observed between λ -FLCs and testosterone levels, no correlation was indeed found with HOMA-IR index. These data confirm high levels of FLCs in PCOS, suggesting systemic inflammatory state and a possible role in the pathophysiology of such complex syndrome.